Afetna Point, Saipan : archaeological investigations of a Latte Period village and historic context in the Commonwealth of the Northern Mariana Islands /: archaeological investigations of a Latte Period village and historic context in the Commonwealth of the Northern Mariana Islands. (2019) - Dixon, Boyd; Walth, Cherie; Mowrer, Kathy; Welch, Danny
No abstract available